Multi-criteria decision making for determining best teaching method using fuzzy analytical hierarchy process - Xu, Sheng-li; Yeyao, Tang; Shabaz, Mohammad (Soft computing (Berlin, Germany), 2023)
During the outbreak of COVID-19, information technology played a critical role in promoting education all around the world. Online teaching boosts students' learning processes and has a good impact on their learning during the epidemic. Big data technology transforms traditional teaching approaches and learning processes by providing a rich learning resource for diverse teaching elements and improving teachers' teaching techniques. Due to the COVID-19 epidemic, online education spread quickly, and traditional instruction was abruptly switched to online mode, posing a number of issues for students and management. Choosing a decent teaching technique is not an easy option, and it is even more difficult when it comes to selecting the approach. We used the Fuzzy Analytical Hierarchy Process (Fuzzy AHP) method to evaluate four instructional methods based on seven criteria to solve this challenge. Fuzzy AHP is a powerful, simple, and direct way for determining which approach is the most efficient and effective. To simplify the selection process and address the issue of uncertainty, the Fuzzy AHP technique employs the geometric mean method. The Fuzzy AHP approach was found to be efficient and successful in the decision-making process in this study.